Disaster Mitigation Based on Review Articles in Sustainable Development Models in Indonesia - bin Fauzi, Rosmadi; Angel Hidayat; Paus Iskarni; L. Sukardi (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Natural disasters are one of the main challenges facing Indonesia which can threaten the sustainability of development and community welfare. This research aims examines the role of Geographic Information Systems (GIS) in the literature review applied to disaster mitigation as part of a sustainable development model in Indonesia. The methodology used includes spatial analysis and secondary data collection regarding disasters that occurred in various regions. The research results show that the use of GIS in articles read can increase efficiency in disaster risk mapping, spatial planning and data-based decision making. In addition, the integration of GIS in disaster mitigation strategies can strengthen the resilience of society and the environment in Indonesia. This research recommends capacity building and collaboration between government, communities and stakeholders to maximize the potential of GIS in disaster mitigation and achieve sustainable development goals with One of the important goals in the SDGs is Goal 11: Sustainable Cities and Communities, which encourages disaster-resilient development, as well as Goal 13: Climate Action, which emphasizes the importance of adaptation and mitigation measures to climate change.